Rural poverty report 2011 : new realities, new challenges : new opportunities for tomorrow's generation (International Fund for Agricultural Development RomeIT, 2010)
Looks at who the rural poor are, what they do and how their livelihoods are changing. Explores the challenges that make it so difficult for rural people to overcome poverty and identifies opportunities and pathways that could lead towards greater prosperity - now and in the future.
Keywords: POVERTY